UPAYA MENINGKATKAN LOYALITAS PELANGGAN SKINCARE SKINTIFIC DI KABUPATEN SUMBAWA MELALUI STRATEGI CUSTOMER EXPERIENCE - Sucihati, Roos Nana; Budiman, Desita Adelia (Samalewa: Jurnal Riset & Kajian Manajemen, 2025)
This study aims to examine efforts to increase customer loyalty of skintific skincare in Sumbawa District through customer experience strategies. The type of this study was associative study which aims to determine the effect of customer experience strategy (X) on the loyalty of Skintific skincare customers in Sumbawa District (Y). The type of data used in this study was quantitative obtained directly from primary sources using a research instrument in the form of a questionnaire. Respondents in this study were 50 Skintific skincare customers in Sumbawa District, totalling 50 people. The selection of respondents was determined using non probability sampling techniques with a accidental sampling (convenience sampling) method. The data analysis techniques used was simple linear regression analysis, partial hypothesis testing (t-test), and coefficient of determination testing (R2). The results of the study showed that customer experience strategy had a positive and significant effect on customer loyalty of Skintific skincare in Sumbawa District. These results suggest that the better of customer experience strategy implemented, the more loyalty of Skintific skincare customers in Sumbawa District will increase. Conversely, the worse of customer experience strategy implemented, the more the loyalty of Skintific skincare customers in Sumbawa District will decrease. The customer experience strategy contributes to effected the loyalty of Skintific skincare customers in Sumbawa District was 46.5%, while the remaining of 53.5% was effected by other factors not examined in this study, such as product quality, service quality, and promotions.